Green synthesis of glyco‐phenol by enzymatic coupling between ferulic acid and glucosamine: An ecofriendly procedure. (5th July 2021) - Aljawish, Abdulhadi; Chevalot, Isabelle; Paris, Cedric; Muniglia, Lionel
Abstract: A new glyco‐phenol was produced by the coupling between glucosamine (Glu) and ferulic acid (FA) using Myceliophthora thermophila laccase as biocatalyst in mild conditions (distilled water and 30°C) as an environmentally friendly process. Results indicated that the enzymatic reaction created a new derivative (FA–Glu), produced from coupling between Glu and FA by covalent bonds. By the high production of (FA–Glu) derivative and its stability, the optimal ratio of (FA:Glu) was of (1:1) at optimal time reaction of 6 h. Under these optimal conditions, almost 55% of ‐NH2 groups on Glu were bound with FA oxidation products. The new derivative showed higher hydrophobic character than Glu due to the presence of FA in its structure. Liquid chromatography–mass spectrometry analysis showed that (FA–Glu) derivative exhibited a molecular mass at MM 713 g/mol containing one Glu molecule and three FA molecules after decarboxylation. Furthermore, the new derivative presented good antioxidant and antiproliferative activities in comparison with Glu and FA. These results suggest that the enzymatic conjugation between Glu and FA is a promising process to produce a new glyco‐phenol having good functional properties for potential applications.